2018
DOI: 10.1002/jbm.a.36586
|View full text |Cite
|
Sign up to set email alerts
|

Balancing biofunctional and biomechanical properties using porous titanium reinforced by carbon nanotubes

Abstract: Despite the well‐known advantages of the titanium‐based implant systems, they still lack an optimal balance between biofunctionality and mechanical strength, especially regarding the modulation of cellular response and a desired implant osseointegration. In this work, we fabricated a nanocomposite based on porous commercially pure grade 4 titanium (c.p. Ti) reinforced with carbon nanotubes (CNT) at 5% and 10% w/w, with the aim of obtaining a nanocomposite with lower stiffness compared to traditional titanium‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Some authors combined PLA with carbon nanotubes (CNTs) because CNTs advantageously improve the degradation rate as well as the mechanical and electrical properties of polymers (Hasanzadeh et al, 2019;Irfan et al, 2019;Khoramishad, Khakzad, & Fasihi, 2017;Kim, Zare, Garmabi, & Rhee, 2018;Pavón et al, 2019;Roy, Petrova, & Mitra, 2018;Simonovic et al, 2018;Zare & Rhee, 2017a;Zhang et al, 2018). Chen et al (2013) reported a high degradation rate in poly(Llactide)/CNTs nanocomposites, which largely depended on the CNT content.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors combined PLA with carbon nanotubes (CNTs) because CNTs advantageously improve the degradation rate as well as the mechanical and electrical properties of polymers (Hasanzadeh et al, 2019;Irfan et al, 2019;Khoramishad, Khakzad, & Fasihi, 2017;Kim, Zare, Garmabi, & Rhee, 2018;Pavón et al, 2019;Roy, Petrova, & Mitra, 2018;Simonovic et al, 2018;Zare & Rhee, 2017a;Zhang et al, 2018). Chen et al (2013) reported a high degradation rate in poly(Llactide)/CNTs nanocomposites, which largely depended on the CNT content.…”
Section: Introductionmentioning
confidence: 99%